Sample Preparation Technique for Scanning Electron Microscopy in Analyzing Shrimp Shell Biodegradation by Actinomycetes through Solid-State Fermentation - Widyastuti Widyastuti; Annisa Ananda; Rohimatul Anwar; Kurniawan Shidiq (Lembaga Pengembangan Kinerja Dosen, 2025)
Shrimp shell waste is a chitin-rich biopolymer with high potential for microbial bioconversion into value-added products. This study aimed to analyze the microstructural degradation of shrimp shells by the actinomycete isolate 18D38A1 under solid-state fermentation, using Scanning Electron Microscopy (SEM). A fresh sample preparation method was applied, involving washing and immersion in 70% ethanol, followed by vacuum drying and gold sputter-coating. Fermentation was conducted over a period of 1 to 4 days. SEM analysis revealed progressive structural deterioration of the shrimp shell matrix, including increased surface erosion, pore formation, and breakdown of chitin fibers, which became more pronounced each day. These observations indicate active and time-dependent biodegradation by isolate 18D38A1. The sample preparation protocol proved effective in preserving morphological features and enhancing SEM image clarity, enabling precise visualization of degradation stages. The combination of solid-state fermentation and optimized SEM preparation provides a reliable approach to evaluate the biodegradation process of chitinous waste by actinomycetes over time. This study demonstrates a practical SEM sample preparation method for visualizing the progressive biodegradation of shrimp shell by actinomycete isolate 18D38A1 from day 1 to day 4.